GEOLOGIC AND HYDROGEOLGIC ASPECTS OF THE THERMAL AQUIFER SYSTEM IN ARGENTINEAN EASTERN CHACOPARANENSE BASIN - Angel, Silva Busso Adrián (Águas Subterrâneas, 2000)
The following work is a summary of the pricipal geologic aspects and hydrogeologic of the Thermal Aquifers contained by the Botucatú Formations and Serra Geral in the oriental region of the Watershed Chacoparanense Argentina and their correlation with the geologic units and similar hiyrogeologic in the western region of the Oriental Republic of Uruguay. In the Oriental Republic of Uruguay studies have been carried out previously partial tending to the quantification of the Hydrotermal Resourse and their possibilities, (TAHAL, 1986, HIDROSUD, 1988, Montanio and Carrion, 1990; Catteno, 1992; Montyear Xavier and Collazo Caraballo, 1998). During the last years a geologic and hydrogeologic study has been carried out in the institutional mark of the INA with the support of the UNESCO that gave place to the realization of a doctoral thesis in the University of Buenos Aires, (Silva Busso, 1999). Starting from this last one the author has summarized the general aspects in this work including the hydrogeologic map of the Thermal Aquifer System and recommendations for its future exploration and exploitation and an estimated evaluation of the resource. The objective of this study is the correlation and geologic and hydrogeologic interpretation, in a regional context, as a consequence of the childbirth in the Argentinean sector